THE IMPROVEMENT OF PROCUTION EFFICIENCY FOR CRISPY SNACK WITH SPINNER INVERTER AND DOUBLE CONE - Dewi Maya Maharani (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Brawijaya, 2017)
Crispy product is one kind of snack food that is currently quite popular in the community. In the Batu City, there are some SMEs processed products of crispy such as tofu, crispy, mushrooms, chicken and potatoes. There are 2 members SMEs that manufacture processed form of crispy tofu and mushrooms with crispy are Kentaki Digadho and Crispy Mushrooms. The problem faced by SMEs partners crispy processed is still low productivity due to limited production means that the majority of the manual so that the need for the introduction of production technology can improve production efficiency. In the production of crispy tofu and mushrooms require production facilities in the form of Mechanical Mixer (Food Mixer), Spinner and Packaging Continuous Sealer to improve the quality and quantity of production of processed crispy so that production can be maximized the demand. For this time, SMEs can improve production efficiency and improve production capacity to improvement of existing production systems by facilitating machinery equipment production technology with a working system that save time, energy and production costs. In addition SMEs can improve the crispy product packaging to be more energized with the diversification of product packaging.